Hubungan Pengetahuan Dan Sikap Tentang K.E.P (Kurang Energi Protein) Dengan Perilaku Orang Tua Dalam Meningkatkan Status Gizi Balita K.E.P di Kota Manado - Nurlela Hi. Baco; Universitas; Rukmini Harun (Jurnal Medika Nusantara, 2023)
Lack of Protein Energy (K.E.P) will occur when the body's need for calories, protein or both is not fulfilled by the diet. Many factors influence the occurrence of K.E.P including the knowledge and attitudes of parents of toddlers in improving the nutritional status of toddlers. The purpose of this study was to determine the relationship between knowledge and attitudes of parents of toddlers about K.E.P (Energy Protein Deficiency) with parents' behavior in improving the nutritional status of toddlers in Manado City. The design of this study used the Correlation Descriptive method with a cross-sectional approach, the population was all parents who had toddlers in the city of Manado with 51 people with the sample technique being total sampling, data collection using a questionnaire. Data were analyzed using the chi square statistical test with a significance of ?=0.05 using a computerized program. The results of the univariate analysis found that 51% of respondents had moderate knowledge about K.E.P, 52.9% of respondents had a negative attitude, 52.9% of respondents had inappropriate behavior. After the statistical tests were carried out, the p value was 0.004, meaning that there was a relationship between knowledge and parental behavior. The p value was 0.012, meaning that there was a relationship between parental attitudes and parental behavior. From the results above it can be concluded that there is a significant relationship between knowledge and attitudes of mothers and parents' behavior in improving the nutritional status of toddlers so it is suggested to the land to provide counseling about health, especially K.E.P and evaluate it because it will influence parental behavior.